Learning Experience of Chinese Nursing Students during Clinical Practicum: A Descriptive Qualitative Study - (Anson) (MDPI AG, 2021)
The change in clinical environment can have a significant impact on nursing students' clinical learning and as a consequence, to their competency. Students' learning experiences could provide important insights for improving the existing approach towards clinical education. This descriptive qualitative study aimed to explore nursing students' clinical learning experience. Focus group interviews were conducted with 20 final year nursing students studying a bachelor nursing programme at a self-financing tertiary institution in Hong Kong. Thematic analysis was conducted. 16 female and four male students were recruited. Six themes were identified: Anxiety towards clinical practicum, expectations of roles and responsibilities in practicum, ward environment, adequacy of support, learning attitude, and practicum arrangement. The findings suggest that nursing students are more discontented with their clinical training than before. Nursing faculty must look for possible ways to improve the clinical learning environment.